Hubungan Antara Hukum dan Etika dalam Politik Hukum di Indonesia (Membaca Pancasila sebagai Sumber Nilai dan Sumber Etik) - Sri Pujiningsih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2017)
The purpose of the Indonesian state is contained in the Constitution of 1945 paragraph IV. Achieving the goals together should be designed, formulated and agreed with all the elements of the nation in the teacher called legal politics. The establishment of legal instruments is the final activity of public policy which includes the legislation process. Applied ethics which is a branch of philosophy that discusses about human behavior, in this paper is human in the state. The purpose of this page is to know the relationship between law and how and how to find law and ethics in the Political Law in Indonesia. The legal political formulation was 15 years after independence through the TAP MPRS. 2 of 1960 on the outline of the National Development Plan of the Universe Planning was then changed to State Policy Guidelines (GBHN) which renewed for 5 (five) years. Meanwhile, the relationship between ethics and law can be seen from 3 (three) dimensions, namely the dimension of substance and container, the dimension of relationship breadth shows and the human dimension to realize or violate it.Keywords: Law and Ethics, Political Law, Pancasila